Kajian Hakikat, Tujuan, dan Aliran Filsafat Pendidikan dalam Kurikulum MBKM - Imanuel A. W. Chrismastianto; I Wayan Lasmawan; I Gusti Putu Suharta; I Wayan Kertih (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2023)
The internet science and technology development, artificial intelligence, and nanotechnology is currently the result of human thinking in building civilization on earth. Of course in response to this, the education curriculum needs serious attention from the government in order to achieve the goals and be able to adapt to the intended developments. This paper aims to analyze the nature, goals, and schools of educational philosophy in the MBKM Curriculum as material for thought and discussion in order to produce relevant and contextual recommendations for efforts to improve the education quality in Indonesia which is able to adapt to developments in science and technology. The method used in writing this article is a qualitative research method of library research (library research) through literature studies that are relevant to the nature, goals, schools of educational philosophy in the MBKM curriculum. Based on the results of the studies that have been conducted, it shows that the MBKM curriculum adheres to the philosophy of humanism, pragmatism, existentialism, and critical pedagogy because learning tends to be instilled student centered learning and the learning process is autonomous and flexible in a higher education environment with an innovative learning culture and adapted to the needs of students.